REseau MOllusques des Rendements Aquacoles huitre creuse (REMORA) - Fleury, Pierre-gildas; Cornette, Florence; Claude, Serge; Palvadeau, Hubert; Robert, Stephane; D'Amico, Florence; Le Gall, Patrik; Vercelli, Catherine; Pien, S (2003)
The monitoring network IFREMER /REMORA is assessing, on a yearly basis, mortality, growth and quality criteria of two oyster batches ("juveniles" = one-year old and "adults" = two-years old), distributed among various stations of the main French oyster areas. Samplings are carried out in March, June, September and December. This network is a tool for trend estimations (geographic and chronological, on the national scale) it must not be considered as an accurate estimation of professional oyster ongrowings. In 2001, mortality mainly occured in Summer on "adults" in baie des Veys (Normandy) and on juveniles in Cancale and Pénerf (Brittany) and in Fouras and Marennes (Poitou-Charentes). With an average individual weigh of 59 g in December, 2001 has been a year of poor growth. Best growths have occurred (as usual) in the baie des Veys (BV02), the Aber Benoît, Pen-Bé and the lagoon of Thau in the Mediterranean Sea. For juveniles there were no great difference, excepted a lack of growth in the baie de Bourgneuf. With regard to the quality of oysters in December : - Meat index : best indices were obtained in baie des Veys and St-Vaast in Normandy, Aber Benoît in North Brittany, isle of Ré and Ronce (South of Marennes area) and the lagoon of Thau - Polydora : Infestation began in Summer as usual, excepted in Arcachon where it was earlier. Some sites were still badly infected (Index > 0.4) but on the whole, the infestation has regressed compared to previous years. Le réseau IFREMER /REMORA évalue chaque année la mortalité, la croissance et des critères de qualité de 2 lots d'huîtres ("juvéniles" = 1 an et "adultes" = 2 ans) qui sont répartis entre différentes stations dans les principaux secteurs ostréicoles français. Des échantillonnages sont effectués en mars, juin, septembre et décembre. Ce réseau est un outil d'évaluation des tendances (géographiques et chronologiques, globales à l'échelle nationale) il ne doit pas être perçu comme un estimateur précis des croissances obtenues chez les producteurs. En ...